Does prism adaptation treatment reduce spatial neglect and improve function? - Chen, Peii; Hreha, Kimberly; MacPhee, Catrina; Salter, Amber; Eskes, Gail A. (Frontiers in Rehabilitation Sciences, 2025)
The potential of using prism adaptation for treating spatial neglect (SN) was questioned when recent meta-analyses found inconsistent evidence. However, analyses of clinical datasets support the use of prism adaptation treatment (PAT) in reducing SN and improving function. The main objective of this review is to evaluate the current state of the evidence of PAT therapeutic effects, identify knowledge gaps, and make suggestions to guide further research and support clinical decision-making. We used the framework of the National Institutes of Health (NIH) Stage Model for Behavioral Intervention Development which provides guidance on best practices for developing effective behavioral interventions that can be implemented in real-world settings. This model emphasizes the interplay between mechanisms underlying therapeutic effects (“who” should receive the treatment and “how” best does it work?) and considerations of adaptability and feasibility in real-world settings. The present critical review led to the following conclusion: the use of the NIH Stage Model reveals the heterogeneity of PAT studies and challenges in advancing PAT as an effective intervention. The key mechanisms such as prism strength, treatment intensity, arm visibility and activities during treatment, and evaluation methods lack consensus. Therefore, clinical research teams must continue to collect evidence to determine critical mechanisms and the optimal protocol. Further research identifying the optimal PAT protocol is needed before another meta-analysis on PAT's clinical efficacy should be conducted again.